Ten Years of Boko Haram in Nigeria
VI, 183 p.
Keywords: This book provides a contemporary overview of Boko Haram's activities. Since Boko Haram emerged in 2002, media-driven narratives as well as social scientific methodologies have been increasingly applied to draw generalisable conclusions on what goals the groups have pursued, what strategies it has used for these purposes and the counter campaign strategies authorities have pursued. But from 2009 to 2018, Boko Haram has pursued high-intensity violence: assassinations, bombing, kidnappings, beheading or threats of violence, conscriptions and territorial occupation. This makes it imperative to deepen and broaden our understanding of the groups’ activities toward a problem-solving and policy-relevant analysis. Previously published in Security Journal Volume 33, issue 3, September 2020.